Jordan Peele : Us - Harvey, Shannon; Michaels, Adam (Los Angeles: Inventory Press, 2024)
A masterpiece of identity horror and a dark reflection on America’s past and present, this companion paperback to the critically-acclaimed film Us features Oscar®-winning director Jordan Peele’s screenplay illustrated with over 150 stills from the motion picture; deleted scenes; an introduction by the filmmaker; and in-depth annotations. These include texts by hannah baer, Theaster Gates, Jamieson Webster, Jared Sexton, Mary Ping, Shana Redmond, and Leila Taylor, alongside excerpts from Naomi Klein, Coleson Whitehead, Maggie Nelson, Carol J. Clover, Michael Harrington, and Paul Laurence Dunbar, and a constellation of images, definitions, and inspirations that extend the themes of the film. (provided by publisher)
Jordan Peele (born 1979) is an American writer, director and producer. Peele’s directorial debut, Get Out (2017), earned him an Academy Award for Best Original Screenplay as well as nominations for Best Picture and Best Director. In 2012, Peele founded Monkeypaw Productions, which amplifies traditionally underrepresented voices and unpacks contemporary social issues, while cultivating artistic, thought-provoking projects across film, television and digital platforms, including the critically acclaimed horror epics, Us (2019), and Nope (2022). (provided by publisher)
boek
Keywords: Peele, Jordan